2016
DOI: 10.1021/acs.langmuir.6b03474
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adsorption Phenomena in Cubic Tricalcium Aluminate Dissolution

Abstract: The workability of fresh Portland cement (PC) concrete critically depends on the reaction of the cubic tricalcium aluminate (CA) phase in Ca- and S-rich pH >12 aqueous solution, yet its rate-controlling mechanism is poorly understood. In this article, the role of adsorption phenomena in CA dissolution in aqueous Ca-, S-, and polynaphthalene sulfonate (PNS)-containing solutions is analyzed. The zeta potential and pH results are consistent with the isoelectric point of CA occurring at pH ∼12 and do not show an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 54 publications
7
71
0
Order By: Relevance
“…17 By directly tracking the evolution of the surface topography with time, VSI accesses the true dissolution rate of a dissolving solid. [23][24][25] The dissolution rates were quantified using a so-called raindrop procedure*, 17 by which the solution's pH and composition remain essentially constant over the course of the experiment. [23][24][25] The dissolution rates were quantified using a so-called raindrop procedure*, 17 by which the solution's pH and composition remain essentially constant over the course of the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 By directly tracking the evolution of the surface topography with time, VSI accesses the true dissolution rate of a dissolving solid. [23][24][25] The dissolution rates were quantified using a so-called raindrop procedure*, 17 by which the solution's pH and composition remain essentially constant over the course of the experiment. [23][24][25] The dissolution rates were quantified using a so-called raindrop procedure*, 17 by which the solution's pH and composition remain essentially constant over the course of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19][20] The technique features significant advantages over methodologies that are based on analysis of solution compositions because it is unaffected by complexities including: (i) inaccurate knowledge of the solid's surface area, or the presence of particles that are distributed over a wide sizerange, 20 (ii) metastable barrier formation that may be relevant to glassy systems, 21 (iii) incongruent dissolution, 22 and/or (iv) ion adsorption on dissolving or reacting surfaces. [23][24][25] The dissolution rates were quantified using a so-called raindrop procedure*, 17 by which the solution's pH and composition remain essentially constant over the course of the experiment. The typical l/s (liquid-to-solid mass ratio) used was on the order of 50 000 for a contact time of approximately 5 minutes per raindrop cycle for a minimum 74 -*It should be noted that in the rain-drop procedure, while the "bulk" undersaturation of the solution with respect to the dissolving solids will change negligibly, the reduction in undersaturation of the solution may be more substantial in close proximity (i.e., within the first 10 nm) of the solid surface.…”
Section: Methodsmentioning
confidence: 99%
“…Though, there is still no consensus on which chemical species or surface complex is responsible for passivation of the C 3 A surface. Some studies have argued that the passivation layer comprises of SO 2− 4 ions 12,34 ; although, results contradicting this argument have been presented in a study conducted by Collepardi et al 41 Other studies [37][38][39] , have reported that Ca-Al-SO 3 complexes, that preferentially adsorb onto the Alrich C 3 A surface, are responsible for passivating it.…”
Section: Stage Imentioning
confidence: 99%
“…Notably, X‐ray synchrotron analysis and other examinations of C 3 A particulates' surfaces have shown that a metastable calcium aluminate hydrate phase does form on C 3 A surface; however, this phase does not appear to inhibit dissolution of C 3 A or the transport of ions from C 3 A surface to the contiguous solution. In other studies, a surface passivation mechanism has been theorized to be at the origin of retardation of C 3 A hydration during the period when ettringite crystals grow at a slow rate. Though, there is still no consensus on which chemical species or surface complex is responsible for passivation of the C 3 A surface.…”
Section: Review Of Hydration Of C3a In [C3a + C$ + H] Pastesmentioning
confidence: 99%
See 1 more Smart Citation